Penguatan Strategi Pemasaran Digital Produk Home Decoration Pada UMKM Corrie Galery Kelurahan Sawojajar Kecamatan Kedungkandang Kota Malang - Yuliana, Rachma; Rokhmawati, Dian; Yuniarto, Eko (Jurnal ABM Mengabdi, 2024)
Corrie Gallery makes various products made from fabric and thread as well as soap-based products, such as wall decorations that have value or are called "Valuable Products", that is, apart from being wall decorations, these decorations also have a fragrant scent which is complemented by the aroma of therapeutic oil to make it smell good. room. Corrie Gallery has been established for the last 5 years under the leadership of Mr. Andhik Dharmabakti is the owner of the UMKM Home Decoration and Fashion Corrie Gallery in the Handicraft business sector which is located at the Sawojajar Permai Shop Block A No 30, Sawojajar Village, Kedungkandang District, Malang City. This product from Corrie Gallery is made in such a way with a variety of designs and a combination of materials so that it becomes a product that has artistic value and selling power. Apart from Home Decoration Products, Corrie is also trying to develop Fashion Products, namely Women's batik clothes which are elegantly designed and have been displayed in several Fashion Show activities. The problem that has been agreed upon lies in digital marketing and product marketing that is less than optimal so that people do not recognize the products produced even though there are many kinds of products that are needed by the public. And marketing digitalization, namely studying digital marketing through social media, mass media and other supporting technologies. Get to know the market and audience to get to know more about the diversity of products produced. Using social media to build Brand Awareness so that Corrie Gallery can be known by the public both on social media and offline customers who come directly to the gallery. The approach method for this community service activity is educational, namely an interactive discussion followed by a question and answer session as a means of transferring knowledge to empower participants. The results achieved are of course a wider market because of this service activity, Corrie Gallery, sales automatically increase, they are better known to the public, they can develop products that are more popular with the consumer market.